Aproximación al estudio del surf desde una perspectiva de marca. El caso de los surfistas españoles y su relación con el branding. [An approach to the study of surfing from a brand perspective. The case of Spanish surfers and their relationship with branding]. - Paloma Sanz-Marcos (Ramón Cantó Alcaraz, 2019)
This investigation describes what kind of consequences and relationships are established between surf brands and their consumers through the analysis of the discourse of the responsible for those brands and surfers. It is a novel and unexplored subject that, in the specific Spanish case, is non-existent, being the first work carried out in this field. For this purpose, in addition to reviewing the academic literature about branding and surfing, different research techniques of a qualitative nature have been combined. On the one hand, 11 in-depth interviews were conducted with the managers of the most representative surf brands operating in the Spanish market, and, on the other hand, 4 focus groups were held with a total of 29 participants from relevant clusters of the peninsular Atlantic. The results indicate that there is a communicational disconnection that warns of the absence of relationships between brand professionals and their consumers, mainly due to a categorical problem manifested in a lack of sophistication of the professionals who manage it.